2020
DOI: 10.1088/1751-8121/abb042
|View full text |Cite
|
Sign up to set email alerts
|

On the phase transition in the sublattice TASEP with stochastic blockage

Abstract: We revisit the defect-induced nonequilibrium phase transition from a largely homogeneous free-flow phase to a phase-separated congested phase in the sublattice totally asymmetric simple exclusion process with local deterministic bulk dynamics and a stochastic defect that mimicks a random blockage. Exact results are obtained for the compressibility and density correlations for a stationary grandcanonical ensemble given by the matrix product ansatz. At the critical density the static compressibility diverges whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…It should be noted that figure 15 provides a generic picture which seems to be valid for other cases of α and β in the P αβ regime close to ε c1 . It is generally believed and it has been shown that shocks can perform random walks along the x-axis [42,43,45]. At the microscopic level the structure, location and diffusion of a shock can be examined by simulations quite accurately and is discussed in the following.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that figure 15 provides a generic picture which seems to be valid for other cases of α and β in the P αβ regime close to ε c1 . It is generally believed and it has been shown that shocks can perform random walks along the x-axis [42,43,45]. At the microscopic level the structure, location and diffusion of a shock can be examined by simulations quite accurately and is discussed in the following.…”
Section: Discussionmentioning
confidence: 99%
“…a discontinuity in the density profile which can perform random walks along the x-axis. The phenomenon of phase separation in equilibrium systems has its non-equilibrium analog in models of the driven lattice gas [42][43][44][45].…”
Section: Data Availability Statementmentioning
confidence: 99%
“…For self-containedness we recall the precise definition of the process and some of its basic stationary properties which were proved in [33,57,58,63] and used extensively in this work.…”
Section: The Dstasep With a Slow Sitementioning
confidence: 99%
“…As shown in [57], the matrix product ansatz of [63] can conveniently be reformulated in terms of two-dimensional unit matrix 𝟙 and the matrices…”
Section: Stationary Matrix Product Measure (Mpm)mentioning
confidence: 99%
See 1 more Smart Citation